Systematic review of implemented technologies on e-commerce and banking platforms for data protection laws compliance - Bayona Silva, Eduardo Emmanuel; Segura Marcelo, Nathaly Mariel; Ancajima Miñán, Victor Angel; Casaverde Pacherrez, Luis Alberto (LACCEI, 2025)
Exist Diverse technologies that are implemented on E-commerce and Banking platforms to comply with the data protection laws and ensure operational efficiency. However, strengths and weaknesses were identified in its implementation which affect its effectiveness. Therefore, the objective of this study is to analyze the main technologies used on these platforms for compliance with regulations such as the General Data Protection Regulation and California Consumer Privacy Act and evaluate their impact on operational efficiency. A non-experimental, descriptive, qualitative-quantitative design was used, corresponding to a systematic literature review without meta-analysis. Thirty-five articles from Scopus, Redalyc, and Web of Science databases were selected, following inclusion-exclusion specific criteria. The results show that key technologies such as encryption and identity management are fundamentals for regulatory compliance, but face challenges related to high integration costs, technical capacitation, and cultural resistance in some regions. It concludes that although these technologies allow good compliance with data protection laws, their effectiveness varies according to regulatory framework and region. It’s recommended to promote technological innovation and intersectoral cooperation to overcome economic and operative barriers, thus ensuring a more efficient digital platform regulatory compliance.